2003
DOI: 10.1152/jn.01173.2002
|View full text |Cite
|
Sign up to set email alerts
|

Neuromotor Noise Limits Motor Performance, But Not Motor Adaptation, in Children

Abstract: Children do not typically appear to move with the same skill and dexterity as adults, although they can still improve their motor performance in specific tasks with practice. One possible explanation is that their motor performance is limited by an inherently higher level of movement variability, but that their motor adaptive ability is robust to this variability. To test this hypothesis, we examined motor adaptation of 43 children (ages 6-17) and 12 adults as they reached while holding the tip of a lightweigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 42 publications
6
66
0
3
Order By: Relevance
“…However, our results indicate that age is the better predictor of re-learning than variability in the motor pattern. This is consistent with previous work from our group and others (Takahashi et al 2003), which showed that increased movement variability did not limit motor adaptation (i.e., learning). Furthermore, in adults increased motor variability during baseline was found to facilitate same-day learning during reaching adaptation (Wu et al 2014).…”
Section: Learning Rates and Re-learningsupporting
confidence: 93%
“…However, our results indicate that age is the better predictor of re-learning than variability in the motor pattern. This is consistent with previous work from our group and others (Takahashi et al 2003), which showed that increased movement variability did not limit motor adaptation (i.e., learning). Furthermore, in adults increased motor variability during baseline was found to facilitate same-day learning during reaching adaptation (Wu et al 2014).…”
Section: Learning Rates and Re-learningsupporting
confidence: 93%
“…So silent conditions (LI in this experiment) may be associated with under-arousal so that noise may elevate arousal to a more optimal level; thereby increasing task performance [24]. Another suggestion of this improvement is about adaptation with moderate levels so that rats can have an appropriate attention and good performance [6,13,25,26].…”
Section: Discussionmentioning
confidence: 93%
“…For example, noise impairs human task performance most likely in the case of unexpected bursts of noise presented during tasks, whether it involves the continuous intake of new information [1,2], and also the psychomotor task impaired by brief experimentally imposed noise in human [3]. In contrast of these studies, It has been shown that addition of an appropriate amount of noise can improve signal detection in a nonlinear system called stochastic resonance [4]; human hearing and the ability of encoding temporal information can increase by noise [5][6][7]. Nevill et al [8] found that crowd noise influenced referee's decisions at favor of the home team.…”
Section: Introductionmentioning
confidence: 99%
“…Among other topics, research on human motor control focuses on motor adaptation within a changing environment (e.g., Shadmehr & Mussa-Ivaldi, 1994), age-related learning (e.g., Takahashi et al, 2003), generalization and transfer of skills from one movement to another (e.g., Conditt, Gandolfo, & Mussa-Ivaldi, 1997;Oakley & O'Modhrain, 2005), internal versus external focus during task execution (e.g., Criscimagna-Hemminger, Donchin, Gazzaniga, & Shadmehr, 2003;Shadmehr & Moussavi, 2000), and internal movement representation (e.g., Haruno et al, 2001;Todorov, 2004). To investigate these topics, researchers have developed devices that provide haptic interaction and assess a subject's performance simultaneously.…”
Section: Haptic Feedback: Many Concepts Few Proofsmentioning
confidence: 99%